Embryonic and post-embryonic development of the polyclad flatworm Maritigrella crozieri; implications for the evolution of spiralian life history traits - Rawlinson, Kate A (BioMed Central, 2010)
BACKGROUND: Planktonic life history stages of spiralians share some muscular, nervous and ciliary system characters in common. The distribution of these characters is patchy and can be interpreted either as the result of convergent evolution, or as the retention of primitive spiralian larval features. To understand the evolution of these characters adequate taxon sampling across the Spiralia is necessary. Polyclad flatworms are the only free-living Platyhelminthes that exhibit a continuum of developmental modes, with direct development at one extreme, and indirect development via a trochophore-like larval stage at the other. Here I present embryological and larval anatomical data from the indirect developing polyclad Maritrigrella crozieri, and consider these data within a comparative spiralian context. RESULTS: After 196 h hours of embryonic development, M. crozieri hatches as a swimming, planktotrophic larva. Larval myoanatomy consists of an orthogonal grid of circular and longitudinal body wall muscles plus parenchymal muscles. Diagonal body wall muscles develop over the planktonic period. Larval neuroanatomy consists of an apical plate, neuropile, paired nerve cords, a peri-oral nerve ring, a medial nerve, a ciliary band nerve net and putative ciliary photoreceptors. Apical neural elements develop first followed by posterior perikarya and later pharyngeal neural elements. The ciliated larva is encircled by a continuous, pre-oral band of longer cilia, which follows the distal margins of the lobes; it also possesses distinct apical and caudal cilia. CONCLUSIONS: Within polyclads heterochronic shifts in the development of diagonal bodywall and pharyngeal muscles are correlated with life history strategies and feeding requirements. In contrast to many spiralians, M. crozieri hatch with well developed nervous and muscular systems. Comparisons of the ciliary bands and apical organs amongst spiralian planktonic life-stages reveal differences; M. crozieri lack a distinct ciliary band muscle and flask-shaped epidermal serotonergic cells of the apical organ. Based on current phylogenies, the distribution of ciliary bands and apical organs between polyclads and other spiralians is not congruent with a hypothesis of homology. However, some similarities exist, and this study sets an anatomical framework from which to investigate cellular and molecular mechanisms that will help to distinguish between parallelism, convergence and homology of these features.